REFLEKSI AKHIR TAHUN DI SATUAN PENDIDIKAN (SMP PRIMBANA MEDAN) - Rusmin Saragih; Gultom, Imeldawaty; Sitompul, Juliana Naftali; Harahap, Ricky Ramadhan; Barany Fachri (LKP KARYA PRIMA KURSUS, 2023)
Primbana Medan Middle School is one of the schools selected in the driving school program. Primbana Middle School received training from facilitators from the driving school program. Every month this school attends a meeting with the facilitator via zoom meeting/google meet to evaluate the results of the independent learning curriculum at the school. At the end of the 2022/2023 academic year, a year-end reflection was held to assess how the results of the Free Learning Curriculum program were at the school. The teaching method that we use is group discussion so that it makes it easier for fellow teachers to explain the results of reflection on learning according to the subject group taught and explained using cardboard that has been completed by the school, then fellow teachers explain in turn to see the effect in teaching in a better direction. Fellow teachers are better prepared for the demands of the independent learning curriculum and are more prepared to carry out activities related to the independent learning curriculum. Students are better prepared and trained to explore the basic knowledge they have and can develop it.